PENGARUH ISLAMICITY PERFORMANCE INDEX DAN ISLAMIC SOCIAL REPORTING TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA - Fatmala, Kiki; Wirman, Wirman (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
AbstractThis study aims to test empirically the effect of the Islamic performance index and Islamic social reporting on financial performance as proxied by Return on assets. The research was conducted at Islamic Commercial Banks registered with the Financial Services Authority in 2014-2019 with the sampling method using purposive sampling. The analysis method used is multiple linear regression. The results of hypothesis testing in this study indicate that partially the profit sharing ratio has no effect on financial performance. Zakat performance ratio has a positive effect on financial performance and Islamic social reporting has a negative effect on financial performance. Simultaneously, profit sharing ratio, zakat performance ratio and Islamic social reporting have a positive effect on financial performance Keywords : Profit Sharing Ratio; Zakat Performance Ratio; Islamic social reporting ; financial performance